On Estimating the Transition Probabilities: A Case Study - Sutawanir Darwis; Kuslan Kuslan (Institut Teknologi Bandung, 2008)
In actuarial science, a multistate process deals with the joint distribution of two random variables: time until termination and cause of the termination. In a three state process (active, retired, death), an insured in active state canbecome retired according to a force of decrement of retired, insured in retired state can move to death state accordingto a force of decrement of mortality. The main issues are the development of the estimation methods for transitionprobabilities and its implementation on a real data set. Analytical studies of multistate model are well developed in theliterature. However, the empirical studies based on real data set rarely reported. Furthermore, published works focusedon modeling the transition probabilities as function of period of transition. This work presents an extension of transitionprobabilities as function of age of insured and period of transition. A case study of modeling three state process andmethodology for estimating the model parameters from an insurance database under constant forces of decrement ispresented. The forces of decrement was estimated using single decrement moment estimation procedure, and yields atransition probability for a three state models. This paper aims to contribute to the development of empirical transitionprobabilities of multistate model based on real data set as an alternative to the traditional approach to doubledecrement modelling.